Fluoroethylthiolation of indoles with iodofluoroethane. (23rd November 2021) - Leng, Faqiang; Huang, Jianjian; Yu, Nianhua; Wang, Guizhao
Graphical abstract: Abstract: The direct fluoroethylthiolation of indoles with iodofluoroethane was developed. The new unexplored CHx Fy CH2 I/Na2 S2 O4 /PPh3 system proceeded under mild condition to afford the relevant fluoroethylthiolated indoles from good to excellent yield. The simple and efficient strategy offers exciting opportunities for the discovery of fluoroalkylthiol moiety introduction.